2022
DOI: 10.1039/d1tc05922j
|View full text |Cite
|
Sign up to set email alerts
|

Realization of the electric-field driven “one-material”-based magnetic tunnel junction using van der Waals antiferromagnetic MnPX3 (X: S, Se)

Abstract: Presently a lot of efforts are devoted to the investigation of new two-dimensional magnetic materials, which are considered as promising for the realization of the future electronics and spintronics devices....

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…In our previous studies, ,, we have shown that PBE + U + D2 performs very good when studying structures and electronic and magnetic properties of MPX 3 materials, including pristine FePS 3 and FePSe 3 . Here, we employ the same approach to get better insight into the properties of the mixed FePS 1.5 Se 1.5 material under study.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, ,, we have shown that PBE + U + D2 performs very good when studying structures and electronic and magnetic properties of MPX 3 materials, including pristine FePS 3 and FePSe 3 . Here, we employ the same approach to get better insight into the properties of the mixed FePS 1.5 Se 1.5 material under study.…”
Section: Resultsmentioning
confidence: 99%
“…Negative J corresponds to the antiparallel orientation of magnetic moments. Because of the relatively large van der Waals gaps between CoPS 3 single layers ( d > 3.2 Å), the interlayer magnetic coupling between monolayers is very weak and can be neglected. , The magnetic coupling parameters evaluated within the 2D CoPS 3 monolayer (see Figures S1 and S2) take the following values: J 1 = −3.76 meV, J 2 = −0.19 meV, and J 3 = −0.84 meV. With all negative exchange parameters J , these results indicate that the CoPS 3 monolayer is in a robust AFM-Néel phase.…”
mentioning
confidence: 83%
“…Recently, a new class of vdW layered materials, namely transition metal phosphorus trichalcogenides (MPTs), with the structural formula MPX 3 (M: transition metal ion; X: chalcogen, such as S or Se) has attracted increased attention. The bulk MPX 3 crystals are usually crystallized in the C 2/ m or R normal3̅ space groups for X = S and X = Se, respectively, and the single layer is similar to the one of MoS 2 with one-third of transitional metal ions replaced by P–P dimer oriented perpendicular to the layer. Thus, in such MPX 3 monolayers the M ions form the honeycomb lattice. According to previous reports, most MPTs are antiferromagnetic (AFM) semiconductors with a band gap ranging from 1.3 to 3.5 eV, making them promising materials for different application areas, such as spintronics and catalysis. ,, Among other MPTs, several previous works have indicated that CoPS 3 has a great potential in electrocatalysis with a band gap of ≈1.5 eV. , CoPS 3 shows the highest efficiency in oxygen and hydrogen evolution reactions (OER and HER), where exfoliated CoPS 3 was proven to be a promising catalyst for the OER since it could reach the lowest potential of 234 mV at a current density of 10 mA/cm 2 and then maintain high current densities with an overpotential of 388 mV …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From the electronic and magnetic structure point of view, all MPX 3 materials are antiferromagnetic (AFM) wide band gap semiconductors. The magnetic ordering can be Heisenberg AFM-Neél for MnPX 3 with T N ≈ 87/61 K (S/Se), Ising zigzag for FePS 3 with T N ≈ 123 K, or XXZ zigzag for NiPS 3 with T N ≈ 158 K, respectively. The band gap for these materials are in the range of 1.3–3.5 eV depending on the M and X combination .…”
mentioning
confidence: 99%